From Law Book to Legal Book: The Origin of a Species - Michael Widener (Rechtsgeschichte - Legal History, 2021)
This article responds to the question posed in the title of the 18 June 2020 workshop of the Max Planck Institute for European Legal History: »What is a Legal Book? Crossing Perspectives between Legal History and Book History«. Bridging the gap between legal history and book history requires a broader conception of legal literature, one that the term »legal book« captures more accurately than the narrower »law book«. The ﬁeld of legal history has begun to take greater interest in legal books as social and cultural phenomena, as objects of commerce and as artifacts. The article develops a deﬁnition of »legal book« using illustrations of law books that are taken from the books themselves, including allegorical images, author portraits, and depictions of lawyers at work. These images highlight the book’s function in law as symbol, text, and artifact. The article concludes by pointing to opportunities for collecting, research, and teaching that the broader deﬁnition of »legal book« presents for curators and the historians they serve.